2010
DOI: 10.1089/rej.2010.1043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polyphenolic Antioxidants in Health, Disease, and Aging

Abstract: Polyphenolic antioxidants from dietary sources are frequently a topic of interest due to widespread scientific agreement that they may help lower the incidence of certain cancers, cardiovascular and neurodegenerative diseases, and DNA damage and even may have antiaging properties. On the other hand, questions still remain as to whether some antioxidants could be potentially harmful to health, because an increase in glycation-mediated protein damage (carbonyl stress) has been reported in some cases. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 114 publications
(108 reference statements)
1
90
0
Order By: Relevance
“…The context-dependent effect of resveratrol on lifespan apparently is not a unique feature of resveratrol. Phytochemicals found in fruits and vegetables have been shown to be beneficial to health, promote healthy aging, and possibly longevity (Lithgow et al 2005;Obrenovich et al 2010). Emerging evidence indicates that prolongevity effects of phytochemicals depend on dietary conditions of the organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The context-dependent effect of resveratrol on lifespan apparently is not a unique feature of resveratrol. Phytochemicals found in fruits and vegetables have been shown to be beneficial to health, promote healthy aging, and possibly longevity (Lithgow et al 2005;Obrenovich et al 2010). Emerging evidence indicates that prolongevity effects of phytochemicals depend on dietary conditions of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Other research on the potential for nutritional modulation of lifespan has suggested the possibility that polyphenolic compounds from fruits and vegetables added to diets modulates healthy aging and lifespan (Lithgow et al 2005;Obrenovich et al 2010). For example, resveratrol, a phytoallexin that is a member of the stilbene family, has been shown to extend lifespan in yeast, worms, flies, and a shortlived fish (Howitz et al 2003;Wood et al 2004;Valenzano et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Poly phenols which are organic compounds present in regular human diet have an antioxidant property. [8][9][10] Early men lived in forests and his food habits provided him dietary antioxidants to cope up with ROS but after the initiation of organized farming his food habits changed and now the food habits are completely different with very little dietary derived antioxidants. Moreover human beings are con stantly facing environmental toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are described as having antioxidant (Brunetti et al, 2013;Procházková et al, 2011;Romano et al, 2013) and antigenotoxic activities (Boubaker et al, 2013;Chaabane et al, 2012). In addition, flavonoids have antineoplastic effects and can also protect against cardiovascular and neurodegenerative diseases (Obrenovich et al, 2010;Obrenovich et al, 2011;Simões et al, 2006).…”
Section: Resultsmentioning
confidence: 99%